Preserved Unconscious Processing in Schizophrenia: The Case of Motivation. (25th June 2022) - Berkovitch, Lucie; Gaillard, Raphaël; Abdel-Ahad, Pierre; Smadja, Sarah; Gauthier, Claire; Attali, David; Beaucamps, Hadrien; Plaze, Marion; Pessiglione, Mathias; Vinckier, Fabien
Abstract: Background and Hypothesis: Motivation deficit is a hallmark of schizophrenia that has a strong impact on their daily life. An alteration of reward processing has been repeatedly highlighted in schizophrenia, but to what extent it involves a deficient amplification of reward representation through conscious processing remains unclear. Indeed, patients with schizophrenia exhibit a disruption of conscious processing, whereas unconscious processing appears to be largely preserved. Study Design: To further explore the nature of motivational deficit in schizophrenia and the implication of consciousness disruption in this symptom, we used a masking paradigm testing motivation both under conscious and unconscious conditions in patients with schizophrenia ( n  = 31) and healthy controls ( n  = 32). Participants were exposed to conscious or subliminal coin pictures representing money at stake and were subsequently asked to perform an effort-task by squeezing a handgrip as hard as possible to win this reward. Study Results: We observed a preserved effect of unconscious monetary rewards on force production in both groups, without any significant difference between them. By contrast, in the conscious condition, patients with schizophrenia were less sensitive to rewards than controls. Our results confirm that unconscious incentives have effects on exerted forces in the general population, and demonstrate that patients with schizophrenia exhibit a dissociation between an impaired conscious motivation and a preserved unconscious motivation. Conclusions: These findings suggest the existence of several steps in motivational processes that can be differentially affected and might have implication for patient care.